Time-restricted feeding rescues high-fat-diet-induced hippocampal impairment - Jennifer A. Davis; Jodi R. Paul; Stefani D. Yates; Elam J. Cutts; Lori L. McMahon; Jennifer S. Pollock; David M. Pollock; Shannon M. Bailey; Karen L. Gamble (iScience, 2021)
Summary: Feeding rodents a high-fat diet (HFD) disrupts normal behavioral rhythms, particularly meal timing. Within the brain, mistimed feeding shifts molecular rhythms in the hippocampus and impairs memory. We hypothesize that altered meal timing induced by an HFD leads to cognitive impairment and that restricting HFD access to the “active period” (i.e., night) rescues the normal hippocampal function. In male mice, ad-lib access to an HFD for 20 weeks increased body weight and fat mass, increased daytime meal consumption, reduced hippocampal long-term potentiation (LTP), and eliminated day/night differences in spatial working memory. Importantly, two weeks of time-restricted feeding (TRF) at the end of the chronic HFD protocol rescued spatial working memory and restored LTP magnitude, even though there was no change in body composition and total daily caloric intake. These findings suggest that short-term TRF is an effective mechanism for rescuing HFD-induced impaired cognition and hippocampal function.